Kafala v. Human Rights Migrant Workers at the 2022 Qatar World Cup - Gunawan, Yordan; Akbar, M. Fabian; Corral, Eva Ferrer (Journal of Indonesian Legal Studies, 2024)
The research analyzes violations of human rights against immigrant workers at the 2022 Qatar World Cup. After receiving the privilege of hosting the 2022 World Cup, Qatar was faced with the problem of migrant workers, which has become a concern of the world community. Migrant workers who build infrastructure face discriminatory and exploitative treatment, and hundreds of migrant workers are found working on infrastructure development for the 2022 World Cup, where workers are affected by human rights violations by the companies where they work. The problem is due to the existence of the Kafala system, which is considered to be the root cause of all aspects of the migrant workforce in infrastructure development in Qatar through 2022. The research method used is normative legal research with a case approach. The results of the study show that the sponsorship kafala system implemented by Qatar only facilitates the occurrence of modern slavery through the exploitation of the rights of migrant workers. Therefore, the research examines Qatar's actions on human rights violations and the International Labour Organization (ILO) accountability in efforts to influence policies related to migrant workers in Qatar.